Dos #brequesdosapps às associações de entregadores: a percepção dos trabalhadores sobre a resistência à Uberização no trabalho por aplicativos - Ricarte, Camila de Sousa (2023)
This research aims to investigate the emergence of resistance movements of delivery drivers from delivery apps, recognizing them as associations for the defense of economic, political, social and professional interests of workers in this sector. Starting from the initial assumption that the labor environment of these workers is situated in precariousness, the theoretical dialogue with some authors of Social Psychology of Work (SPW) is justified, since the performance in this theoretical line is guided by the focus on work phenomena from the perception of workers. We have as objectives to analyze the context of emergence of the “Breques dos aplicativos”, in its historical-political relations with neoliberalism and with other workers' movements. To achieve these intentions, we interviewed app deliverers in the cities of Fortaleza - CE and Brasília - DF, anchored in the contributions of SPW for data analysis, extracting in our study the uniqueness of the activity from the perception of the interviewed deliverers. From the critical understanding of the contradictions in the world of work, considering the power relations at play in the researched activity, as well as the historical specificity and the peculiarities of the moment of capitalism, we debug from this the conditions pointed out by our interlocutors. Among the results are the indications that the bonds formed in their struggles lead to the formation of Workers' Associations as a means to carry out the workers’ claims and as one of the possible destinations in which the Breques ended up.